Genotyping of Escherichia Coli Isolated From Clinical and Hospitals Environment - Abd ALameer, Rana (University of Thi-Qar Journal of Science, 2015)
Pathogenic Escherichia coli (E. coli) strains are known to cause intestinal and extraintestinal infections in human. A wide variety of infectious diseases could be caused by E. coli strains, including urinary tract infection, septicemia, newborn meningitis, central nervous system and respiratory system infections.Several bacterial agents can cause diarrheal and urinary tract infections, among these E.coli strains are detected as an important cause of morbidity and mortality of diarrhoea and UTI throughout the world.A total of 318 samples were collected during the period from September 2012 to march 2013 .All specimens were screened for the presence of E. coli by cultured on MacConkey agar and Eosin-methylene blue agar then identified by biochemical tests and confirmed by API 20E system which revealed that:90/318(28.33%) gave positive growth for E.coli )15 (16.63%) environmental isolates and 75(83.33%) clinical isolates( as fallowing:1/42(2.38%)was obtained from burns,7/25(28%)from High vaginal swabs ,11/41 (26.82%) from Wounds infections,18/33(54.54%)from Diarrheal infections and38/67(56.71 %)from Urinary tract infections, while 15/110 (13.63%) from environmental isolates, The isolated were subjected to molecular identification as E.coli by used the intergenic spacer region primer(ITS). The confirmed isolates were examined to detect the phylogenetic group based on triplex PCR by using a combination of two genes (chuA and yjaA) and an anonymous DNA fragment.Universal primers (ITS) indicated that all isolates 90(100%) gave positive results.The phylogenetic analysis revealed that 90 E.coli isolates belonged to three phylogenetic groups A &D 36(40%)for each, while B2 18 (20%) and no one isolates belong to B1 phylogenetic types .